At the Boundaries of 18th-Century Russian Portraiture - Karev, Andrey A. (Actual Problems of Theory and History of Art, 2020)
The consideration of the boundaries of 18th-century Russian portrait painting is usually associated with the study of the nature and originality of the phenomenon, which involves a look from the inside out. Meanwhile, the consideration of the “boundary” area itself could provide information about contacts with “neighbors”and the opportunities provided by the time and patron. The18th-century Russian portrait painting has been chosen as an example because it by the end of the century accumulated the highest achievements in national artistic culture.Special attention has been paid to the lower chronological boundary, which lies between the late medieval “personа” and the portraiture of modern times. Arrangement of the “side” boundaries of portraiture is connected with the addition of a full system of genres encouraged by the Imperial Academy of Arts. Among other genres, the allegory became one of the most widely used in portraiture. Having already appeared in the 18th century, the era of classicism, allegory became the important link between the portrait image and historical painting. When comparing two images of the same person, for example, a monarch in portraiture versus allegorical painting, a change is observed in the status of a hero towards greater historization. Another variant of the boundary area is created by the interaction between a model figure and landscape background. The appearance of “promenade-portrait” with a fairly developed landscape environment coincided in Russia with the formation of the landscape as a separate “kind of painting”. A portraiture approach to staffage canbe considered a symptom of the beginning of the convergence of these genres. The influence of genre painting on portraiture was not great because genre painting itself was not well developed in 18th-century Russia. In general, the example of the portraiture form shows that the boundaries of the genre are the subjects of certain convention and their transparency is the testament of the living memory of the former syncretic integrity and the sign of readiness for a new synthesis.
Keywords: age of classicism; painting; picture; genre boundary; portraiture; allegory; landscape; genre